Model Interkoneksi Nilai Islam, Regulasi Sosial, Dan Tradisi Kesehatan Melalui Kuliah Tamu Internasional: Penguatan Kesadaran Kritis Mahasiswa Uis Malaysia - Lisa Aminatul Mukaromah; Nawafila Februyani; Agus Sholahudin Shidiq; Mohd Izzudin (Journal of Research Applications in Community Service, 2025)
Global developments demand cross-border learning models that are not only academic in nature but also capable of integrating religious values, social regulations, and modern scientific knowledge in understanding contemporary issues. However, studies examining how international guest lectures can serve as a medium to interconnect these three aspects remain limited, thereby highlighting the need for research that illustrates the pedagogical and social contributions of cross-national community engagement. This study aims to analyze how students at Universiti Islam Selangor (UIS) Malaysia comprehend current issues through the perspectives of Islamic values, social regulations, and culturally rooted health traditions in an international guest lecture setting. This research employed a qualitative descriptive method using participant observation, document analysis, and reflective interactive discussions. The activity took place at DK Ishak Baharom, UIS Malaysia, involving 70 students and featuring three lecturers from Indonesia who presented topics on: (1) legal regulations for combating online gambling, (2) zakat as an Islamic financial instrument and social policy, and (3) traditional jamu and herbal medicine as components of culturally based modern healthcare. The findings indicate that students developed a comprehensive understanding of: (a) the prohibition of online gambling, which is grounded not only in economic considerations but also in moral and spiritual dimensions; (b) zakat as an empowerment instrument requiring effective regulation to generate meaningful social impact; and (c) herbal traditions as cultural heritage aligned with the halal–thayyib principles and supported by scientific legitimacy. Measurable outcomes include enhanced critical awareness, strengthened Islamic literacy related to contemporary issues, and positive participant responses reflected in high enthusiasm and analytical questioning during discussions. This study affirms that international guest lectures can serve as a transformative model of cross-border community engagement, strengthening academic collaboration while providing an integrative learning space that connects Islamic values, social regulations, and modern scientific knowledge.